Atrophy of the Vagus Nerve in Parkinson's Disease Revealed by High-Resolution Ultrasonography - Walter, Uwe; Tsiberidou, Panagiota; Kersten, Maxi; Storch, Alexander; Löhle, Matthias (Frontiers in Neurology, 2018)
Background: The vagus nerve has been suggested to represent one major route of disease progression in Parkinson’s disease (PD). Here, we examined whether patients with idiopathic PD exhibit an atrophy of the vagus nerve in comparison to age-matched controls. Methods: In this cross-sectional study, performed between July 2017 and January 2018, we measured the caliber (cross-sectional area) of the mid-cervical vagus, accessory and phrenic nerves in 20 patients with PD (disease duration: 10.1±7.4 years) and 61 (including 20 age-matched) controls using high-resolution ultrasonography. Ultrasonography and assessments of autonomic function were performed by blinded raters. Results: Mean vagus nerve calibers were lower in patients with PD compared to age-matched controls (right: 0.64±0.17 vs. 1.04±0.20; left: 0.69±0.18 vs. 0.87±0.15 mm2; p<0.001) while accessory and phrenic nerve calibers did not differ. In controls, age correlated negatively with calibers of the accessory and the phrenic nerve (each p≤0.001), and trended to correlate with vagus nerve caliber (p=0.023). In patients with PD and age-matched controls combined, the summed caliber of the right and left vagus nerves correlated with the burden of autonomic symptoms on the PD Non-Motor Symptoms Questionnaire (r=-0.46; p=0.003). Moreover, the caliber of the right but not of the left vagus nerve correlated with the parasympathetic domain of heart rate variability (r=0.58; p=0.001). Conclusions: PD is associated with a bilateral atrophy of the vagus nerve but not of the spinal accessory or the phrenic nerves. Our findings suggest that viscero-afferent and viscero-efferent vagal fibers are predominantly affected in PD.